(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Urinary tract infection (UTI) is one of the most common bacterial infection in humans and a major cause of morbidity. Most commonly, members of Enterobacteriaceae family, particularly the uropathogenic strains of Escherichia coli is the primary causative organism of UTIs in different parts of the world. The aim of this retrospective study was to determine the frequency of uropathogens in different age groups of both sex and to evaluate Escherichia coli as predominant bacteria for urinary tract infection in women with their antimicrobial sensitivity pattern. A total of 1616 urine samples were collected during January to December, 2012, from patients attending at Delta Medical College & Hospital, Dhaka and analyzed for different uropathogens. Urine cultures were carried out and the isolates were identified by standard procedures as needed. Antimicrobial susceptibility testing was performed by disk diffusion method according to ‘The Clinical Laboratory Standard Institute’ (CLSI) guidelines. In this present study, prevalence of uropathogens were higher in female patients (77.2%) than male patients (22.8%). The isolates were Escherichia coli (80%), Klebsiella spp. (7.9%), Enterococcus spp. (4.9%), Staphylococcus saprophyticus (2%), Proteus (1.4%), Pseudomonas spp. and Staphylococcus aureus (1.2%). The rate of Escherichia coli infection in females of reproductive age group; 15-50 years was higher (61%) and in that only a particular age group (21-30) was more prone to this pathogen (22.9%). Among the drugs used for testing the antimicrobial susceptibility, Imipenem, Amikacin, Nitrofurantoin and Gentamycin were found to be effective in the treatment of urinary tract infection. As drug resistance to commonly used antimicrobials is increasing, improvement in overall sanitary condition, proper knowledge on personal hygiene would play an important role in reducing the incidence and occurrence of urinary tract infection. J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 13-18